Prevalência de sintomas do transtorno dismórfico corporal em abdominoplastia, rinoplastia e ritidoplastia - Rocha, Maria José Azevedo de Brito [UNIFESP] (2011)
INTRODUCTION: Body dysmorphic disorder (BDD) and comorbid mental disorders may compromise the visual perception of body parts, causing dissatisfaction in patients, who may consult a plastic surgeon. OBJECTIVE: To identify the level of dissatisfaction with appearance and prevalence of BDD symptoms in a population of candidates to three plastic surgical procedures. METHODS: Three-hundred patients of both sexes were allocated into three groups: abdominoplasty (GA) (n=90), rhinoplasty (GR) ( n=151), and rhytidoplasty (Grit) ( n=59). Each group was subdivided into two sub-groups: patients without BDD symptoms (n=39; n=72; n=34) and patients with BDD symptoms (n=51; n=79; n=25), according to the Body Dysmorphic Disorder Examination (BDDE), which was administered preoperatively. RESULTS: The prevalence of BDD symptoms in GA, GR and GRit was 57%, 52%, and 42%, respectively. Significant associations were found between BDD symptoms, degree of body dissatisfaction, and sexuality inhibition in the three groups. GA patients were the most dissatisfied with appearance and had the greatest number of BDD symptoms compared with the other groups (GR, GRit). GRit had the greatest percentage of patients with severe symptoms (64%), followed by GA (59%) and GR (38%). CONCLUSION: The candidates to the three plastic surgical procedures had high prevalence of BDD symptoms. GA showed the highest degree of body dissatisfaction and greatest number of BDD symptoms, GR had the lowest percentage severe cases, and Grit had the highest percentage of severe cases.